2002
DOI: 10.1111/1469-7610.00054
|View full text |Cite
|
Sign up to set email alerts
|

The severity and nature of motor impairment in Asperger's syndrome: a comparison with Specific Developmental Disorder of Motor Function

Abstract: This study is consistent with others suggesting a high prevalence of clumsiness in Asperger's syndrome. Our findings also attest to the widespread prevalence of motor impairment in developmental disorders and the problems such co-morbidity poses for attempts to posit discrete and functionally coherent impairments underlying distinct syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
199
3
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(233 citation statements)
references
References 60 publications
23
199
3
8
Order By: Relevance
“…Green, Baird, Barnett, Henderson, Huber, & Henderson, 2002]. In the present study, using the more recent MABC-2 test battery, the ASD group scored significantly lower than the TD group in both of these component areas, but the SLI group had a very similar level of deficit across both areas as well.…”
Section: Discussioncontrasting
confidence: 46%
“…Green, Baird, Barnett, Henderson, Huber, & Henderson, 2002]. In the present study, using the more recent MABC-2 test battery, the ASD group scored significantly lower than the TD group in both of these component areas, but the SLI group had a very similar level of deficit across both areas as well.…”
Section: Discussioncontrasting
confidence: 46%
“…It has to be mentioned that in their approach errors that did not occur in more than 10% of the observations were considered as less relevant and not further analyzed regarding group differences. Their finding that reversal errors are exceptional and that an impaired viewpoint transformation cannot explain imitation problems in autism is consistent with the results of the research group of Green (Green, Baird, Barnett, Henderson, Huber, & Henderson, 2002) and Mostofsky (Mostofsky, Dubey, Jerath, Jansiewicz, Goldberg, & 15 Denckla, 2006). In addition, the finding in the study of Mostofsky et al (2006), that children with autism showed a better gesture performance in the imitation condition than on verbal command, supports this view.…”
supporting
confidence: 79%
“…Many studies addressed this question with movement assessment batteries with normative percentiles for performance and objective scoring: for example, the PANESS (Dowell et al, 2009;Dziuk et al, 2007;Floris et al, 2016;Jansiewicz et al, 2006;Mostofsky, Burgess, & Gidley Larson, 2007), the M-ABC or M-ABC2 (Ament et al, 2015;Green, Baird et al, 2002;Green, Moore, & Reilly, 2002;Green et al, 2009;Hanaie et al, 2013;Hanaie et al, 2014;Kopp, Beckung, & Gillberg, 2010;McPhillips, Finlay, Bejerot, & Hanley, 2014;Miyahara et al, 1997;Sumner et al, 2016;Whyatt & Craig, 2012), or the Bruininks-Oseretsky test (Dewey et al, 2007;Ghaziuddin & Butler, 1998;Hilton, Zhang, Whilte, Klohr, & Constantino, 2012;Pan, 2014). These measures yield total scores which were sometimes analysed alone, but they each assess a range of fine and gross motor skills, including balance and gait, hopping or jumping, repetitive sequential movements of the hands and feet, manual dexterity and ball skills (catching and throwing).…”
mentioning
confidence: 99%
“…Ball skills, most notably in catching a ball, are highlighted by numerous reports (Ament et al, 2015;Green et al, 2009, Green, Baird et al, 2002Green, Moore, & Reilly, 2002;Hanaie et al, 2013;Papadopoulos et al, 2012;Staples & Reid, 2010;Whyatt & Craig, 2012). More fine-depth analysis of gait, for example using electronic walkways or infrared cameras and sensors placed on the body (Nobile et al, 2011), corroborate the difficulty that movement batteries report in heel-to-toe walking, and further report gait irregularities (for example greater variance in stride length and velocity), ataxia, reduced range of motion in the joints, and difficulty walking in a straight line.…”
mentioning
confidence: 99%